Chirped Superlattices as Adjustable Strain Platforms for Metamorphic Semiconductor Devices. (25th October 2017) - Chen, Xinkang; Islam, Md Tanvirul; Kujofsa, Tedi; Ayers, John E
Abstract : Chirped superlattices are of interest as buffer layers in metamorphic semiconductor device structures, because they can combine the mismatch accommodating properties of compositionally-graded layers with the dislocation filtering properties of superlattices. Important practical aspects of the chirped superlattice as a buffer layer are the surface strain and surface in-plane lattice constant. In this work we studied two basic types of InGaAs/GaAs chirped superlattice buffers; type I is compositionally modulated while type II is thicknesses modulated. For both types, we have investigated the equilibrium surface strain and surface in-plane lattice constant, and have compared the behavior to linearly-graded buffers having the same top target composition of indium.